2016
DOI: 10.1556/030.63.2016.010
|View full text |Cite
|
Sign up to set email alerts
|

Full-length VP2 gene analysis of canine parvovirus reveals emergence of newer variants in India

Abstract: The canine parvovirus (CPV) infection is a highly contagious and serious enteric disease of dogs with high fatality rate. The present study was taken up to characterize the full-length viral polypeptide 2 (VP2) gene of CPV of Indian origin along with the commercially available vaccines. The faecal samples from parvovirus suspected dogs were collected from various states of India for screening by PCR assay and 66.29% of samples were found positive. Six CPV-2a, three CPV-2b, and one CPV-2c types were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…Our study found that CPV-2b is a prevalent strain in this area. Previously, the dominance of CPV-2b over CPV-2a was supported by other researchers (Parthibhan et al 2012;Srinivas et al 2013;Nookala et al 2016;Sharma et al 2016). In most of the studies covering small regions, the dominance of one strain over the other shows that they are mutually exclusive.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our study found that CPV-2b is a prevalent strain in this area. Previously, the dominance of CPV-2b over CPV-2a was supported by other researchers (Parthibhan et al 2012;Srinivas et al 2013;Nookala et al 2016;Sharma et al 2016). In most of the studies covering small regions, the dominance of one strain over the other shows that they are mutually exclusive.…”
Section: Discussionmentioning
confidence: 78%
“…After its first reporting from India in 1982, CPV-2 has been reported from all over India Nookala et al 2016). The present quantum of prevalence corresponds to earlier reports, where 41.50% (Parthiban et al 2010), 49.00% (Sharma et al 2016), 53.12 % (Parthiban et al 2012) and 53.90 % (Srinivas et al 2013) cases of AGE were attributed to CPV-2 infection, whereas higher involvement of CPV-2, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T324I mutation in CPV-2a strains may be a common amino acid alteration in Asian countries, especially in China [33] and in South America. Mutations at amino acid residue 324 may have an impact on parvovirus host range [38] and it was also been demonstrated that the T324I mutation occurs in regions referring to potentially important antigenic epitopes. This substitution might have a direct influence on viral biology [5].…”
Section: Discussionmentioning
confidence: 99%
“…In India and Iran, the dominant types in recent outbreaks were CPV-2a and -2b [21,72,73] . In 2016, CPV-2c was detected in northern and central India [74,75] and Iran [73] .…”
Section: Prevalence Of Canine Parvovirus Type 2 Variantsmentioning
confidence: 99%